2017
DOI: 10.1016/j.bjid.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization rates, length of stay and in-hospital mortality in a cohort of HIV infected patients from Rio de Janeiro, Brazil

Abstract: In this study, we evaluated trends in hospitalization rates, length of stay and in-hospital mortality in a cohort of HIV-infected patients in Rio de Janeiro, Brazil, from 2007 through 2013. Among the 3991 included patients, 1861 hospitalizations occurred (hospitalization rate of 10.44/100 person-years, 95% confidence interval 9.98–10.93/100 person-years). Hospitalization rates decreased annually (per year incidence rate ratio 0.92, 95% confidence interval 0.89–0.95) as well as length of stay (median of 15 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
3
14
3
Order By: Relevance
“…This finding is in line with the study conducted in Spain, in which 53% of deaths were attributed to AIDS defining illnesses [23]. Similar study from Brazil reported that in-hospital mortality was almost two times higher in AIDS-related hospitalizations than in non-AIDS-related hospitalizations [24]. However, several studies from developed countries reported non-AIDS-related illnesses as being the most common cause of death [2527].…”
Section: Discussionsupporting
confidence: 87%
“…This finding is in line with the study conducted in Spain, in which 53% of deaths were attributed to AIDS defining illnesses [23]. Similar study from Brazil reported that in-hospital mortality was almost two times higher in AIDS-related hospitalizations than in non-AIDS-related hospitalizations [24]. However, several studies from developed countries reported non-AIDS-related illnesses as being the most common cause of death [2527].…”
Section: Discussionsupporting
confidence: 87%
“…The median LOS of 11 days in our study is equal to the median reported by a similar study in Brazil [ 39 ]. Shorter LOS was reported by similar studies in Spain (8 days) [ 40 ], United Kingdom (7.5 days) [ 41 ], and the United States (6 days) [ 42 ].…”
Section: Discussionsupporting
confidence: 66%
“…In Madagascar, incidence rate of tuberculosis was estimated to 237 (153–338) per 100 000 among general population of which 5.6 (2.5–9.8) per 100 000 occurred among HIV positive in 2016 [ 21 ]. A decrease in hospitalizations due to ADE has been observed since widespread of highly active ART use in middle and high-income countries [ 8 , 13 , 22 , 23 ]. However, hospitalization rate and inpatient mortality remained high in Africa despite effective ART scale-up [ 24 ].…”
Section: Discussionmentioning
confidence: 99%